SI SANTRI: PENGELOLAAN PEMBAYARAN UKT MELALUI BOTCLAIM TINGKATKAN KEPUASAN MAHASISWA - Wiwin Yuni Isnaini; Zulfi Zumala Adriani (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
Student satisfaction in UKT payments is not only determined by the speed of transactions, but by the transparency and ease of access provided by digital systems such as Botclaim. This study aims to analyze UKT Payment Management Through Botclaim or application in Improving Student Satisfaction at KH Muktar Syafaat Banyuwangi University, which is under the auspices of a boarding school. Before the implementation of Botclaim, the UKT payment system at this university was still done manually, which caused various administrative problems, data input errors, and inconvenience for students. The research method used is a quantitative approach involving students and Bauk officers who have used Botclaim to make UKT payments. In determining informants in the study using purposive sampling technique. Data collection techniques in this study include interviews, observation, and document analysis. Data analysis used is data reduction, data presentation, and conclusion drawing. The results showed that students felt significant improvements such as automation in terms of easy payment and speed that can be seen anytime and anywhere, as well as more confidence in the security of their personal data. In addition, the system also contributes to reducing administrative errors and speeding up the payment verification process. The conclusion of this study is that the implementation of Botclaim in the UKT payment system has successfully increased student satisfaction through increased efficiency, ease of access, and strengthened transaction security.